EXTRACELLULAR SUPEROXIDE DISMUTASE CHANGES IN PATIENTS WITH DIFFERENT BRAIN TUMORS - Hasan, Hathama; Numan, Ali (Iraqi Journal of Science, 2024)
The Specific activity of extracellular superoxide dismutase (EC-SOD) was measured in healthy persons and in patients with benign and malignant brain tumors. The results show decrease of the EC-SOD specific activity in sera of patients with benign and malignant brain tumors in comparison to that of control group.This study concentrated on studying the changes that occur in sera EC-SOD activity of patients with benign and malignant brain tumors, in comparison to that of normal individuals. The result also revealed that this isoenzyme is present in many different molecular weights forms (as judged by polyacrylamide gel electrophoresis), some of these with no enzymatic activity. Conversion among these forms occurs in the malignant sera.